Mical modulates Tau toxicity via cysteine oxidation in vivo. - Prifti, E.; Tsakiri, E.N.; Vourkou, E.; Stamatakis, G.; Samiotaki, M.; Skoulakis, E.M.C.; Papanikolopoulou, K. (Acta neuropathologica communications, 2022)
Tau accumulation is clearly linked to pathogenesis in Alzheimer's disease and other Tauopathies. However, processes leading to Tau fibrillization and reasons for its pathogenicity remain largely elusive. Mical emerged as a novel interacting protein of human Tau expressed in Drosophila brains. Mical is characterized by the presence of a flavoprotein monooxygenase domain that generates redox potential with which it can oxidize target proteins. In the well-established Drosophila Tauopathy model, we use genetic interactions to show that Mical alters Tau interactions with microtubules and the Actin cytoskeleton and greatly affects Tau aggregation propensity and Tau-associated toxicity and dysfunction. Exploration of the mechanism was pursued using a Mical inhibitor, a mutation in Mical that selectively disrupts its monooxygenase domain, Tau transgenes mutated at cysteine residues targeted by Mical and mass spectrometry analysis to quantify cysteine oxidation. The collective evidence strongly indicates that Mical's redox activity mediates the effects on Tau via oxidation of Cys322. Importantly, we also validate results from the fly model in human Tauopathy samples by showing that MICAL1 is up-regulated in patient brains and co-localizes with Tau in Pick bodies. Our work provides mechanistic insights into the role of the Tau cysteine residues as redox-switches regulating the process of Tau self-assembly into inclusions in vivo, its function as a cytoskeletal protein and its effect on neuronal toxicity and dysfunction.